Comparative Analysis of Witness Protection Law in Indonesia, Malaysia, and Australia - Arsawati, Ni Nyoman Juwita; Putri, Luh Putu Yeyen Karista; Wulandari, Ni Gusti Agung Ayu Mas Tri; Tajuddin, Hanifah Haydar Ali; Withnall, Eric Gordon (Journal of Indonesian Legal Studies, 2024)
Witness protection is the cornerstone of an effective criminal justice system. Therefore, it is important to ensure the quality of witness protection law. This study uses normative method to compare witness protection law in Indonesia, Malaysia and Australia. The result shows several similarities and differences in 5 areas namely a) the subject of protection; b) selection process; c) rights and obligations of parties; d) institutional arrangement; and e) criminal sanctions. Each country has its own approach to regulate the witness protection. Indonesia is progressive in terms of giving special rights for 6 different categories of subject of protections. For instance, special right for compensation and restitution for victims of particular crimes. Indonesia also encourage justice collaborator to give evidence by promising leniency, parole or remission. Conversely, Australia explicitly clarify that the witness protection must not be interpreted as rewarding criminals. Unlike Indonesia, Malaysia and Australia grants equal rights for all witness. Despite such differences, these 3 countries have similarity in terms of the imposition of selection process to ensure the protection is prioritized for those who need it the most. The witness protection must be maintained to balance the interest of witness, accuse and the society. The goal is not to give excessive protection for witnesses, but to adjust the protection according to the limitation of resources and financial. Moreover, Indonesia should adopt the disclosure requirement as implemented in Malaysia and Australia to prevent the witness from using the program to circumvent his legal or financial obligations.